EXPECTED ECOLOGICAL FORECASTS IN THE ERA OF GLOBALIZATION - Nasiba Normuminova (Bright Mind Publishing, 2025)
In the era of globalization, ecological issues are becoming increasingly serious. This research examines problems such as global climate change, resource scarcity, and the decline of biodiversity. Expected ecological forecasts and their threats and opportunities for humanity are analyzed. This article provides recommendations to aid in the development of sustainable development strategies and emphasizes the importance of global cooperation.
Keywords: Climate change, global warming, environmental crisis, ecological ethics, sustainable development, Paris Agreement, ecological disasters, technological impact, greenhouse effect, migration flows, natural resources, renewable energy, international cooperation, Swiss Re Institute, environmental responsibility.